Ciborinia camelliae (Sclerotiniaceae) induces variable plant resistance responses in selected species of Camellia - Denton-Giles, Matthew; Bradshaw, R.; Dijkwel, P. (American Phytopathological Society, 2013)
Ciborinia camelliae is the causal agent of Camellia flower blight. This fungal pathogen is a significant pest of the Camellia floriculture industry because it specifically infects the floral tissue of ornamental camellia cultivars leading to the rapid development of necrotic lesions and blight. This study aims to characterize natural resistance to Ciborinia camelliae within a selection of Camellia spp. Based on macroscopic lesion development, Camellia ‘Nicky Crisp’ and Camellia lutchuensis were chosen as compatible and incompatible hosts, respectively. Microscopic analyses of the incompatible Camellia lutchuensis–Ciborinia camelliae interaction revealed several hallmarks of induced plant resistance, including papillae formation, H2O2 accumulation, and localized cell death. The compatible Camellia Nicky Crisp–Ciborinia camelliae interaction failed to trigger a similar resistance response. Ciborinia camelliae growth in compatible tissue demonstrated a switch from biotrophy to necrotrophy, evident from the simultaneous development of secondary hyphae and necrotic lesions. Extension of resistance analyses to 39 additional Camellia spp. identified variable levels of resistance within the Camellia genus. The evidence presented supports a resistance breeding strategy for controlling Ciborinia camelliae on ornamental Camellia hybrids.